2017
DOI: 10.1177/1471082x16681317
|View full text |Cite
|
Sign up to set email alerts
|

A general framework for functional regression modelling

Abstract: Researchers are increasingly interested in regression models for functional data. This article discusses a comprehensive framework for additive (mixed) models for functional responses and/or functional covariates based on the guiding principle of reframing functional regression in terms of corresponding models for scalar data, allowing the adaptation of a large body of existing methods for these novel tasks. The framework encompasses many existing as well as new models. It includes regression for 'generalized'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 106 publications
(216 reference statements)
0
78
0
Order By: Relevance
“…This situation was discussed in the paper by Rodríguez-Álvarez et al (2015b) where the SAP From left to right: results using the SOP method and the functional regression approach by Greven and Scheipl (2017). Solid red line: MS patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This situation was discussed in the paper by Rodríguez-Álvarez et al (2015b) where the SAP From left to right: results using the SOP method and the functional regression approach by Greven and Scheipl (2017). Solid red line: MS patients.…”
Section: Discussionmentioning
confidence: 95%
“…We analyse the DTI dataset, that can be found in the R-package refund (Goldsmith et al, 2016). A detailed description of the study and data can be found in Goldsmith et al (2011), Goldsmith et al (2012) and Greven and Scheipl (2017). In brief, the study aimed at comparing the white matter tracts in patients affected by multiple sclerosis (MS) and healthy individuals.…”
Section: Diffusion Tensor Imaging Scan Datamentioning
confidence: 99%
“…We considered a functional sequence regression model with p functional covariates to determine how p environmental factors influence onion weights n over time [12][13][14]. This model is defined as follows:…”
Section: Methodsmentioning
confidence: 99%
“…As an example of the extensions possible with the discussed model class, we briefly discuss a general framework of functional regression models that we proposed in Scheipl et al (2015Scheipl et al ( , 2016, Brockhaus et al (2015Brockhaus et al ( , 2016 and summarized in Greven and Scheipl (2017), with the accompanying R packages refund (Goldsmith et al 2018) and FDboost (Brockhaus et al 2020) internally using the mgcv and mboost (Hothorn et al 2010) packages for the model fitting, respectively.…”
Section: Functional Regressionmentioning
confidence: 99%